Clinical outcomes of patients treated on the Heidelberg interprofessional training ward vs. care on a conventional surgical ward: A retrospective cohort study. Issue 4 (4th July 2022) - Kuner, Charlotte; Doerr-Harim, Colette; Feißt, Manuel; Klotz, Rosa; Heger, Patrick; Probst, Pascal; Strothmann, Hendrik; Götsch, Burkhard; Schmidt, Jochen; Mink, Johanna; Mitzkat, Anika; Trierweiler-Hauke, Birgit; et al.
ABSTRACT: Interprofessional training wards (IPTW) are a form of interprofessional education enabling trainees of different healthcare professions to work together in teams. Concerns about patient safety are a major barrier to the implementation of IPTWs. The objective of this retrospective study was to analyze patient relevant clinical outcomes on Germany's first IPTW ( Heidelberger Interprofessionelle Ausbildungsstation ; HIPSTA) in the Department of Surgery at University Hospital Heidelberg in comparison to a conventional surgical ward (CSW). The setting is a large tertiary care center with a focus on major oncological surgery. The endpoints were postoperative complications according to the Dindo-Clavien Classification and a set of patient-safety outcomes. In total, 232 patients treated on HIPSTA were retrospectively compared with 465 patients on a CSW. Baseline characteristics were comparable between groups. No significant difference between rate or severity of overall postoperative complications was observed. In-hospital mortality did not significantly differ between groups. However, the mean length of hospital stay was significantly shorter on HIPSTA. Furthermore, HIPSTA patients had less frequent reoperations. Patient safety in surgical IPTW was not compromised in comparison to a CSW, and there were some areas where significantly better outcomes were identified.